Justified by Work: Identity and the Meaning of Faith in Chicago's Working-Class Churches - Bruno, Robert Anthony (Ohio State University Press, 2008)
In Justified by Work, Robert Anthony Bruno sheds light on the simple but rarely asked question: “What role do faith and religious observance play in the everyday lives of working people?” While some historical work has been done on middle-, upper-, and professional-class notions of faith, money, time, and business ethics, the theological beliefs and experiences of working-class Americans have been practically ignored. Bruno’s book is embedded in the contemporary religious practices and beliefs of working-class Chicago-area congregations to show both how faith is inextricably interwoven in the everyday lives of the people who regularly attend places of worship and how class impacts the daily manifestation of these people’s religion (from theology to practice). Most past religious scholarship has drawn a dichotomy between urban and suburban churches and has compared religious observance and denominational membership by race, gender, ethnicity, and recently, around the emergence of a “knowledge” and “entrepreneurial” class forms of church practice. Diverging from previous models, Justified by Work, based on author interviews with a wide spectrum of working-class Chicagoans, offers a comparative study of working-class religious practice and faith, across race and ethnic identity. Christian churches are represented by a Catholic Mexican congregation, an African American Baptist church, and a mixed eastern European church. Bruno examines as well how religious observance affects the lives and attitudes of working-class Jews and Muslims in Chicago.